Determination of optimal solutions for processing operations and for the modules of flexible production systems (FPS) - Todić, Velimir; Banjac, Dragan (Journal of Production Engineering, 1993)
Modern flexible production systems, with their high production technology capabilities, high prices, and investment costs, demand corresponding operating conditions to ensure rational production. For this reason, when designing technological processing procedures for a given group of parts within FPS with a known structure and module characteristics, it is necessary to define the optimal processing conditions and key parameters. Furthermore, in the conceptual design and construction development of FPS and their modules for the production of a given group of parts, it is necessary to establish a solution for FPS that ensures the desired level of technological and economic production effects. This presentation has outlined some of the optimization and selection approaches for technological processing procedures and FPS modules.